Navigating Statelessness: Legal Consequences of Divorce in Mixed Marriages Involving Rohingya Refugees - Elfirda Ade Putri; Windy Sri Wahyuni (JURNAL AKTA, 2026)
This study aimed to examine how Indonesian Private International Law (PIL) addresses the legal vacuum arising from the inapplicability of the nationality principle (lex patriae) in divorce proceedings involving mixed marriages between Indonesian citizens and stateless Rohingya refugees, and to analyze the legal consequences with respect to child custody, division of joint property, and children’s citizenship status. The research method employed was normative juridical research, utilizing statutory, conceptual, and doctrinal approaches combined with grammatical, systematic, and teleological interpretive methods, as well as deductive legal reasoning. The novelty of this research lies in its systematic doctrinal construction of a conflict-of-laws framework applicable to stateless persons within Indonesian PIL, demonstrating how the convergence of lex domicilii, lex fori, and the public policy doctrine collectively resolves the normative gap produced by statelessness. Based on the findings, it can be concluded that the absence of nationality is resolved by substituting lex patriae with the domicile principle (lex domicilii), which in practice converges with lex fori, enabling Indonesian courts to apply the Marriage Law and the Compilation of Islamic Law as lex causae. Child custody is determined by the best interests of the child, joint marital property is divided equitably, and children born from such marriages automatically acquire Indonesian citizenship pursuant to the ius sanguinis principle under Law No. 12 of 2006. Despite substantive legal protection being guaranteed de jure, practical enforcement challenges persist, necessitating stronger administrative and institutional support for effective access to justice.